2014
DOI: 10.1177/1010539514545647
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Risk Factors of Respiratory Symptoms Among Home-Based Garment Workers in Bangkok, Thailand

Abstract: This study aimed to determine the prevalence and risk factors associated with respiratory symptoms. A cross-sectional study with random sampling method was employed and 300 home-based garment workers (HBGWs) were recruited. Risk factors, including personal factors; knowledge, health preventive behaviors, and skill of self-health surveillance, working condition, and respiratory symptoms were assessed. Data were collected using self-reported questionnaires. Prevalence of respiratory symptom was 22.3%. Majority o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…of factories create health hazards (e.g., headache or shoulder pain, backache, joint pain, eye strain, hearing problem, gastroenteritis, chest pain, breathing difficulty, skin disease, tuberculosis, insomnia etc.) among the respondents.Prevalence of occupational health hazards among the respondents: 88.28%.Symptoms of health vulnerabilities:Headache (51%), Joint pain (31%), General weakness (28.3%), Chest pain (26.2%), Backache (24.8%), Gastroenteritis (21.4%), Jaundice (20.7%), Insomnia (20%), Eye strain/problem (13.8%), Hearing problem (8.3%), Skin disease (5.5%), Breathing problem (3.4%), Tuberculosis (2.8%).Causes identified: Bad physical environment; such as noise pollution (33.8%), problem with safe drinking water (15.9%), overcrowding (13.8%), inadequate light (9.7%), dirty (9%), unavailability of separate toilets (5.5%), inadequate ventilation (4.1%); & dusty raw materials of the factories.Psychological health issues are ignored while psychological health is also similarly important such as physical health.ModerateChumchai et al, 2015 [7](Thailand)Prevalence and risk factors of respiratory symptoms among home-based garment workers in Bangkok, ThailandCross-sectional study.Quantitative.Sample size: 300.Male: 66 (22%).Female: 232 (78%).Respondents were selected randomly.Used SPSS for data analysis. Logistic regression analysis was applied to identify risk factors associated with respiratory symptoms.To determine the prevalence and risk factors related to respiratory symptoms.Prevalence of respiratory problems among the respondents is: 22.3%.Common symptoms of respiratory problems:Abnormal lung function (29.3%)Nasal congestion (17.3%)Cough (5%)Itchiness (4.7%)Phlegm (4%)Cough with sputum (1.7%)Chest tightness (0.03%).Allergic symptoms: 25.3%.Causes of respiratory problems/factors associated with respiratory symptoms:Allergic reaction (61.8%) &Fabric dust (61.5%).Ambiguity about sample size: the abstract and methodology say that the size of respondents is 300, however, Table 1 shows that the sample size is 298 (male: 232; female: 66).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…of factories create health hazards (e.g., headache or shoulder pain, backache, joint pain, eye strain, hearing problem, gastroenteritis, chest pain, breathing difficulty, skin disease, tuberculosis, insomnia etc.) among the respondents.Prevalence of occupational health hazards among the respondents: 88.28%.Symptoms of health vulnerabilities:Headache (51%), Joint pain (31%), General weakness (28.3%), Chest pain (26.2%), Backache (24.8%), Gastroenteritis (21.4%), Jaundice (20.7%), Insomnia (20%), Eye strain/problem (13.8%), Hearing problem (8.3%), Skin disease (5.5%), Breathing problem (3.4%), Tuberculosis (2.8%).Causes identified: Bad physical environment; such as noise pollution (33.8%), problem with safe drinking water (15.9%), overcrowding (13.8%), inadequate light (9.7%), dirty (9%), unavailability of separate toilets (5.5%), inadequate ventilation (4.1%); & dusty raw materials of the factories.Psychological health issues are ignored while psychological health is also similarly important such as physical health.ModerateChumchai et al, 2015 [7](Thailand)Prevalence and risk factors of respiratory symptoms among home-based garment workers in Bangkok, ThailandCross-sectional study.Quantitative.Sample size: 300.Male: 66 (22%).Female: 232 (78%).Respondents were selected randomly.Used SPSS for data analysis. Logistic regression analysis was applied to identify risk factors associated with respiratory symptoms.To determine the prevalence and risk factors related to respiratory symptoms.Prevalence of respiratory problems among the respondents is: 22.3%.Common symptoms of respiratory problems:Abnormal lung function (29.3%)Nasal congestion (17.3%)Cough (5%)Itchiness (4.7%)Phlegm (4%)Cough with sputum (1.7%)Chest tightness (0.03%).Allergic symptoms: 25.3%.Causes of respiratory problems/factors associated with respiratory symptoms:Allergic reaction (61.8%) &Fabric dust (61.5%).Ambiguity about sample size: the abstract and methodology say that the size of respondents is 300, however, Table 1 shows that the sample size is 298 (male: 232; female: 66).…”
Section: Resultsmentioning
confidence: 99%
“…Studies revealed some remarkable health issues (that workers develop specifically due to their daily work activities) including respiratory problems [4, 7, 10, 11, 2328], skin diseases/problems [4, 6, 23, 24, 27], musculoskeletal problems [4, 27], hearing loss [24, 27], and cardiovascular diseases [29]. In addition, some frequent and common diseases are reported, including; back/joint pain [4, 10, 2325], cough and common cold [4, 7, 10, 26, 28], headache [10, 23, 24, 26], eye problem and loss of sight [4, 2325], hepatitis (jaundice) [4, 10, 24], fever [4, 11, 26], diarrhea [11, 26, 28], and gastric pain [4, 10]; all which result in RMG workers’ health status becoming vulnerable. Factors reported as contributing to these illnesses and diseases include poor nutritional status and imbalanced diet [4, 11], poverty [26], unhealthy workplace environment [23, 25, 27], and the components of chemical hazards such as dust, smoke, mist, fumes, and dusty raw materials [22, 24].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This study also reported low knowledge levels regarding occupational lung disease, mean score of 7.59±0.89 and low mean prevention practices score of 8.82±3.43. 6 Another study from Nigeria among textile workers reported that most workers had good knowledge (74%), and positive attitude (81%), while only 20% had safe practices. Important predictors of workers' knowledge, and attitude identified by the Nigerian study were formal education, permanent employment and working <5 days a week.…”
Section: Introductionmentioning
confidence: 99%